Animal Welfare Protocols and Labelling Schemes for Broilers in Europe - Papageorgiou, Maria; Tzamaloukas, Ouranios; Simitzis, Panagiotis E (My University, 2025)
Nowadays, consumers are becoming increasingly concerned about the husbandry conditions under which animals are raised, particularly broilers, since broilers are one of the species whose welfare is most impaired in intensive farming systems. One of the primary means of communicating husbandry practices to consumers is through product labelling. Thus, a rising number of animal welfare labelling schemes for broilers are being developed and used across Europe by initiatives of both public and private stakeholders, including NGOs that advocate for animal welfare. This review aims to identify, analyze, and compare these labelling schemes with a focus on the main animal welfare provisions included in them, which contribute to enhanced animal welfare. The schemes were identified through web searches, so that we could visit their official websites, access their standards and regulations and study them in detail. We included in our research only those schemes whose criteria were publicly available. In total, 16 schemes were selected and analyzed. Although these schemes vary in their criteria, they all enhance the welfare standards of broiler production, primarily through incorporating environmental enrichment and/or access to the outdoors. Most schemes define and specify in detail the required animal welfare provisions, setting a clear application frame for the raising period of the birds. However, the welfare of animals during transport and slaughter is often overlooked.
Keywords: Chicken meat; Meat labelling; Broilers; Animal welfare assessment; Environmental enrichment; Positive welfare indicators; Labelling scheme; Animal welfare protocol